EFFECTIVE STRATEGIES TO IMPROVE SPEAKING SKILLS AMONG STUDENTS WHO LEARN ENGLISH AS A FOREIGN LANGUAGE - Xotamova Ominaxon Xabibullo qizi; Obobakirova Valizaoy Valisherovna (TADQIQOTLAR, 2025)
Abstract: Although many students have studied English for years, speaking is still the most intimidating and difficult skill. This article explores why speaking challenges persist among EFL learners and how specific, learner-centered strategies can break this problem. Based on classroom experiences and teacher observations, the article suggests new techniques such as psychological preparation, peer support, spontaneous speaking, and digital storytelling. It is emphasized that effective speech involves not only fluency, but also emotional comfort, self-expression and the ability to overcome fear of making mistakes. This approach offers teachers and students new perspectives on how to speak a foreign language with confidence.